Age-related changes of the tibial nerve cross-sectional area in the disabled elderly - Sandougah, Kholoud J.; Bedewi, Mohamed A.; Alamri, Saeed M.; Alzain, Nawaf A.; Alharthi, Abdulrahman A.; Zayed, Mohammed Ayesh; El-Sharkawy, Mohamed Sherif; Alfawaz, Saleh M.; Alturkistani, Husain; Beheri, Elsayed Abbas; Ali, Rasha; Al-Aqeel, Muneerah; et al. (Frontiers in Neurology, 2026)
ObjectiveThis study aims to assess changes in the cross-sectional area of the tibial nerve in the disabled elderly.Materials and methodsThe study sample included 124 tibial nerves in 62 participants; 16 of which were disabled elderly patients (13 males, 3 females), with a mean age of 66.6, a mean height of 167.1 cm, a mean weight of 83.9 kg, and a mean BMI of 29.9. Twenty-three young controls (6 males, 17 females), a mean age of 48.4, a mean height of 154.9 cm, a mean weight of 79.8 kg, a mean BMI of 32.7, and 23 elderly non-disabled participants (13 males, 10 females), a mean age of 63.6, a mean height of 161.9 cm, a mean weight of 80.56 kg, and a mean BMI of 30.88.ResultsThe mean CSA of the TN in the elderly disabled group was 28.5 mm2. The mean CSA of the young control group’s TN was 20.45 mm2. The mean CSA of the TN in the elderly non-disabled group (both diabetic and non-diabetic) was 27.6 mm2. The mean CSA of the TN in the elderly diabetic non-disabled group was 29.9 mm2. The mean CSA of the TN in the elderly (non-diabetic) non-disabled group was 24.6 mm2.ConclusionIn conclusion, although our study suggests that nerve ultrasound could be a helpful tool for assessment of the tibial nerve in disabled elderly patients, disability status was not an independent predictor of tibial nerve CSA. Future studies with a larger sample size and a homogenous group are suggested.